Shape memory polymer-based prefabricated components: Design ideas and prospects - Zhang, Wencai; Li, Duanling (Frontiers in Materials, 2023)
Shape memory polymers (SMP) are the smart materials that have received the most attention and are the most commonly employed. SMP can be 4D printed to create prefabricated components with transform shapes, properties, or functions under different external excitations. Although smart equipment assembled from these prefabricated components is extensively used in various fields, a systematic overview summary of their design ideas still needs to be provided. This paper briefly analyzes current trends in the design ideas and application of SMP-based prefabricated components. By summarizing two different design ideas: structural combination and material modification, it demonstrates the application of smart equipment assembled from SMP-based prefabricated components in medical, industrial, and aerospace fields. Furthermore, current challenges with both design ideas are discussed.